Utilizing induced neural stem cell‐based delivery of a cytokine cocktail to enhance chimeric antigen receptor‐modified T‐cell therapy for brain cancer - Alex S. Woodell; Elisa Landoni; Alain Valdivia; Andrew Buckley; Edikan A. Ogunnaike; Gianpietro Dotti; Shawn D. Hingtgen (Wiley, 2023)
Abstract Chimeric antigen receptor (CAR)‐modified T‐cell therapy has shown enormous clinical promise against blood cancers, yet efficacy against solid tumors remains a challenge. Here, we investigated the potential of a new combination cell therapy, where tumor‐homing induced neural stem cells (iNSCs) are used to enhance CAR‐T‐cell therapy and achieve efficacious suppression of brain tumors. Using in vitro and in vivo migration assays, we found iNSC‐secreted RANTES/IL‐15 increased CAR‐T‐cell migration sixfold and expansion threefold, resulting in greater antitumor activity in a glioblastoma (GBM) tumor model. Furthermore, multimodal imaging showed iNSC delivery of RANTES/IL‐15 in combination with intravenous administration of CAR‐T cells reduced established orthotopic GBM xenografts 2538‐fold within the first week, followed by durable tumor remission through 60 days post‐treatment. By contrast, CAR‐T‐cell therapy alone only partially controlled tumor growth, with a median survival of only 19 days. Together, these studies demonstrate the potential of combined cell therapy platforms to improve the efficacy of CAR‐T‐cell therapy for brain tumors.